The influence of limited parking availability and pricing on travel pattern to reduce traffic congestion - Awang Sadit, D.D (Universiti Malaysia Sarawak , (UNIMAS), 2005)
The aim of this study is to explore the travel pattern behavior by encouraging people to change their choice of travel mode and time without reducing the number of visitors to come to the commercial centre by using stated preference (SP) technique.